Strengthening Student Discipline Character Education Based on Pencak Silat Extracurriculars - Hidayat, Iman; Hosnan, M; Hakim, Zerri Rahman (LPPM Universitas Primagraha, 2021)
This research intent to know in as much as teacher science about character which be at school especially student discipline character. This era essential have discipline character. Since if character was planted out at deep self student therefore one of it won't outgrow it moral grind zoom or HAM breach (human right), it too looked with presentase that laden by KPAI accepts 26 thousand bulliying's cases 2011 until September 2017. KPAI'S supreme case is front child with law as much 34% one of example it is child violence at Thamrin Citty this case makes education, character and moral at Indonesian as damage. This research utilizes descriptive observational method kualitatif which is a method research that is attributed to figure aught phenomenons. Data collecting utilizes three collecting teches, which is studi observation, interview and documentation. The risearch result inten a character education support disciplined by student gets ektrakurikurer pencak silat's basis at SD sempu's Country 2 Serang City. Pertinent with in as much as which planning learns, the process of teacher and acquired result teacher to character education support student by ektrakurikuler pencak silat's learning.